2018
DOI: 10.1245/s10434-017-6332-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Tumor-Infiltrating Lymphocyte Density Assessed Using a Standardized Method Based on Molecular Subtypes and Adjuvant Chemotherapy in Invasive Breast Cancer

Abstract: Measurements of TIL density in routine clinical practice could give useful prognostic information for the triple-negative, HER2-positive, and luminal B (HER2-negative) IBC subtypes, especially for patients administered adjuvant anthracycline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…Numerous studies have recently quantified immune cell infiltrations in and around tumors. Most of these have used semi-quantitative methods to describe their data such as cell counts per highpower field or per predefined tissue area, positive pixel counts per area, semi-quantitative estimation of TIL numbers or the fraction of TILs in relation to the total intra-tumoral stroma [20][21][22][23][24][25][26]. Data on lymphocytic infiltration in cancers cannot always easily be compared between studies because objective metric data are often lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have recently quantified immune cell infiltrations in and around tumors. Most of these have used semi-quantitative methods to describe their data such as cell counts per highpower field or per predefined tissue area, positive pixel counts per area, semi-quantitative estimation of TIL numbers or the fraction of TILs in relation to the total intra-tumoral stroma [20][21][22][23][24][25][26]. Data on lymphocytic infiltration in cancers cannot always easily be compared between studies because objective metric data are often lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the cut off between TILs high and low groups was 30%, this value allowed for a significant correlation between TILs and different prognostic indicators. Other reports employed different cut off points for this purpose such as 35% cut off in a study by Kotoula et al, in 2016, while Jang and colleagues reported 10% cut off value to define TILs levels that were associated with better outcomes for a subset of hormone positive breast cancer patients [24] [25]. [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the tumor subtype, younger age, black race, unmarried status, uninsured status, and higher pathological grade are relevant factors for the developing of BCSHM in this study and were described earlier as relevant factors for advanced disease 17 - 21 . Some studies also describe possible genetic changes as relevant factors for distant metastasis of BCs 22 . Unfortunately, data on genetics and Ki-67% are not yet available in our study 18 .…”
Section: Discussionmentioning
confidence: 99%